Caracterização do sistema calicreína-cinina durante o processo ovulatório de bovinos - Ilha, Gustavo Freitas (2011)
The kallikrein-kinin system (KKS) has been described as an important mediator of physiologic processes. Kallikreins use kininogen (KNG) as substrate to generate bradykinin, the principal active peptide of the KKS which acts through two types of receptors, the B1R and B2R. The objective of this study was to characterize some components of KKS in different compartments of ovary during the ovulation process in bovine. mRNA expression pattern of KNG, B1R and B2R was assessed in theca and granulosa cells and bradykinin concentration and kallikrein-like activity in follicular fluid of bovine peri-ovulatory follicles. In order to obtain a peri-ovulatory follicle (≥ 12mm), twenty-seven cows were submitted to estrus synchronization protocol and ovariectomized by colpotomy at 0, 3, 6, 12 or 24 hours after a GnRH-analog injection (gonadorelin; 100 μg, IM). Follicular fluid was aspirated for enzymatic assays and granulosa and theca cells were harvested for mRNA analysis. The mRNA expressions in follicular cells were evaluated by real-time RT-PCR and data represented as relative to housekeeping gene cyclophilin. Bradykinin concentration and Kallikrein-like activity was measured in follicular fluid by enzymatic immunoassay and selective substrate cleavage, respectively, and the absorbance measured using a plate reader. KNG mRNA expression was similar for both follicular cell types (P>0.05), while B2R expression in theca cells and B1R expression in theca and granulosa cells showed different profiles during peri-ovulatory period (P<0.05). Bradykinin concentration and kallikrein-like activity in follicular fluid were different (P<0.05) according the time during ovulation process. The results provide an important characterization of the presence and possible regulation of KKS during ovulation in bovine.